Pursuing the New While Sustaining the Current: Incumbent Strategies and Firm Value During the Nascent Period of Industry Change - Eklund, John; Kapoor, Rahul (Organization Science, 2019)
This study considers the nascent period of industry change when the prevalent business model is being threatened by a new model, but there is significant uncertainty with respect to whether and when the new model will dominate. We focus on the challenge of incumbents pursuing both models simultaneously during the nascent period, and the implications on their firms’ valuations. Our theory is premised on the adjustment costs incurred by incumbents associated with the sharing of resources across business models and the conflict between managers vying for limited resources. While firms’ assets and competitive environments are key drivers of their value, we argue that they also impact adjustment costs. Evidence from the U.S. electric utility industry, which is undergoing a change from a centralized to a decentralized model, offers strong support for our arguments. The greater the level of incumbents’ assets that are specific to the existing model, and the greater the level of competition that they face, the lower are their firms’ valuations when investing in the new model relative to when investing in the existing model. Hence, ironically, those incumbents potentially most threatened by the change seem to be least rewarded for their efforts to renew themselves. However, pursuing the new model via alliances can help mitigate adjustment costs. The study uncovers the challenges that incumbents face as they pursue the new model in tandem with the existing dominant model, and helps explain why some incumbents may successfully navigate the changing industry landscape while others may stumble.